Causes Of Cost Overrun and Solutions in Construction Projects in Somalia - Abdi, Ahmed Abdulkadir; Rozlin Zainal (Journal of Technology Management and Business, 2025)
The construction industry plays a critical role in Somalia’s socioeconomic development and has expanded significantly since the end of the civil war; yet, cost overruns remain a major challenge, as many projects exceed their initial budgets. Existing studies indicate that limited skilled personnel, inexperienced managers, and poor communication are contributing factors to this issue. This study aims to identify the causes, solutions, and impacts of cost overruns in Somali construction projects and to analyse the relationships between these variables. A quantitative approach, utilising a structured questionnaire, was employed, yielding 63 valid responses from Grade A contractors, including project managers, engineers, and architects. Descriptive statistics and correlation analysis were used to evaluate the data. The results indicate that unskilled labour, insecurity, lack of insurance, poor project management, and weak infrastructure are the primary causes of cost overruns, while effective cost management, time management, and quality management practices serve as key solutions. Major impacts identified include financial strain on clients, compromised project quality, reputational damage to contractors, and project delays. Correlation analysis revealed a moderate positive relationship between the causes and solutions and a strong positive relationship between the solutions and impacts, suggesting that addressing the root causes is moderately linked to solution effectiveness, whereas implementing the proposed solutions strongly contributes to mitigating the impacts. Overall, the study offers practical insights for improving construction performance and strengthening cost-control mechanisms in Somalia.